2023
DOI: 10.3390/su152316202
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Conservation and Utilization of Landscape Heritage in Modern Urban Parks in Shenyang, China

Na Wang,
Tong Zhang,
Le Li
et al.

Abstract: The transition analysis and type division of landscape heritage are the effective management methods to achieve the overall conservation and targeted utilization of modern urban parks. In this study, Shenyang Zhongshan Park, the first modern urban park in Shenyang, was taken as the research object to explore the historical and cultural value of modern urban parks in Northeast China. The current status and transition characteristics of landscape heritage were analyzed, and the landscape heritage types were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In Shenyang City, northeastern China, based on the IPA model, the authors divided 44 landscape heritages into three subcategories, i.e., already designated for conservation (ADC), should be designated for conservation (SDC), and should be restricted in scale (SRS). They found that (i) ADC was composed of one historic (Chiyoda water tower), two cultural comprehensive (water sources), and three natural (ancient trees) landscape heritages; (ii) SDC was a landscape heritage with long construction age, high importance, poor conservation, and high utilization, which can represent the cultural characteristics of the park and the need to speed up the improvement of its protection system; and (iii) SRS weakened the cultural characteristics of the park, reducing construction intensity to highlight the core themes of the park [21].…”
Section: Theme 3: Utilization and Evaluation Of Urban Forest Landscapementioning
confidence: 99%
“…In Shenyang City, northeastern China, based on the IPA model, the authors divided 44 landscape heritages into three subcategories, i.e., already designated for conservation (ADC), should be designated for conservation (SDC), and should be restricted in scale (SRS). They found that (i) ADC was composed of one historic (Chiyoda water tower), two cultural comprehensive (water sources), and three natural (ancient trees) landscape heritages; (ii) SDC was a landscape heritage with long construction age, high importance, poor conservation, and high utilization, which can represent the cultural characteristics of the park and the need to speed up the improvement of its protection system; and (iii) SRS weakened the cultural characteristics of the park, reducing construction intensity to highlight the core themes of the park [21].…”
Section: Theme 3: Utilization and Evaluation Of Urban Forest Landscapementioning
confidence: 99%